The effect of cleft lip on socio-emotional functioning in school-aged children - Murray, L; Arteche, A; Bingley, C; Hentges, F; Bishop, D; Dalton, L; Goodacre, T; Hill, J; Cleft Lip and Palate Study team (Wiley, 2010)
Children with cleft lip are known to be at raised risk for socio-emotional difficulties, but the nature of these problems and their causes are incompletely understood; longitudinal studies are required that include comprehensive assessment of child functioning, and consideration of developmental mechanisms. Method: Children with cleft lip (with and without cleft palate) (N=93) and controls (N=77), previously studied through infancy, were followed up at 7 years, and their socio-emotional functioning assessed using teacher and maternal reports, observations of social interactions, and child social representations (doll play). Direct and moderating effects of infant attachment and current parenting were investigated, as was the role of child communication difficulties and attractiveness. Results: Children with clefts had raised rates of teacher-reported social problems, and anxious and withdrawn-depressed behaviour; direct observations and child representations also revealed difficulties in social relationships. Child communication problems largely accounted for these effects, especially in children with cleft palate as well as cleft lip. Insecure attachment contributed to risk in both index and control groups, and a poorer current parenting environment exacerbated the difficulties of those with clefts. Conclusions: Children with clefts are at raised risk for socio-emotional difficulties in the school years; clinical interventions should focus on communication problems and supporting parenting; specific interventions around the transition to school may be required. More generally, the findings reflect the importance of communication skills for children's peer relations.